Writing Skills Text Report Observation Results At XI Grade Students At SMA Negeri 2 Tondano - Paath, R C (Universitas Negeri Manado, 2019)
The objectives to be achieved in this study are: (1) To describe the learning steps of the communicative approach in writing descriptive text of the report on the observations of class XI students of SMA Negeri 2 Tondano; (2) To describe the writing skills of the description text of the observation report of the XI grade students of SMA Negeri 2 Tondano by using a communicative approach. The method used is action research according to its type. The subjects of this study were students of grade XI in SMA Negeri 2 Tondano. The source of the data is 20 students and teachers. To collect data the techniques used are tests and observations. Acting in two rounds, the results showed that, in the implementation of the first round of Class XI Language Skills of SMA Negeri 2 Tondano in Writing Text Description of Observation Reports using the communicative approach was still in the range of percentage values of 66.20%, categorized as less able. Based on the unsatisfactory results, the second round was carried out, and the results were in the successful category because they were in the able range of 84.40%. These results indicate that the use of a communicative approach in learning to write descriptive text of the observation report has an impact or can improve the skills of 20 high school students of SMA Negeri 2 TondanoÂ Keywords: Writing skills; report text; observation results.